Unresolved CFD and DEM Coupled Solver for Particle-Laden Flow and Its Application to Single Particle Settlement - Seongjin Song; Sunho Park (Journal of Marine Science and Engineering, 2020)
In the present study, a single particle settlement was studied using a developed unresolved computational fluid dynamics (CFD) and discrete element method (DEM) coupling solver. The solver was implemented by coupling OpenFOAM, the open-source computational fluid dynamics libraries, with LIGGGHTS, the open-source discrete element method libraries. An averaging method using a kernel function was considered to decrease the grid dependency. For the drag model of a single particle, a revised volume fraction with a particle volume expansion coefficient was applied. Falling particles in a water tank were simulated and compared with the empirical correlation. A parametric study using several integrated added mass coefficients and volume expansion coefficients from low to high Reynolds numbers was carried out. The simulations which used the developed numerical methods showed significantly improved predictions of particle settlement.